Determining the temperature field and thermomechanical characteristics of a material, which ensure zero radial stresses in a long hollow cylinder inhomogeneous in the radial direction - Kalynyak, B.M. (Reports of the National Academy of Sciences of Ukraine, 2015)
A method to determine the temperature field and thermo-mechanical characteristics of a material, providing zero radial stresses along a radius in the inhomogeneous long hollow cylinder is proposed. The solution of the corresponding nonclassical steady uncoupled thermoelasticity problem is reduced to solving a Fredholm integral equation of the second kind relative to the temperature. Exact analytical expressions for the temperature field and the concentration of one ingredient of a two-component functionally graded material providing the zero radial and hoop stresses in limits of a simple-mixture model in the absence of mass forces and the axial loading are obtained. The numerical calculations of temperature fields and thermo-mechanical characteristics for real materials are presented.